Transparent Reporting of Pediatric Clinical Trial Interventions : TIDieR-Children and Adolescents - Goren, Katherine; Lai, Veronica Ka Wai; Baba, Ami; Smith, Maureen; Allegaert, Karel; Butcher, Nancy J; Fernandes, Ricardo; Gill, Peter J; Hartling, Lisa; Juszczak, Edmund; Longmuir, Patricia E; Macarthur, Colin; et al. (Pediatrics, 2025)
Pediatric randomized controlled trials (RCTs) inform decisions concerning the choice of interventions in children and adolescents. To enable the implementation of effective interventions, RCT reports need to provide adequate details on the elements, infrastructure, and delivery of these interventions. Using the 12-item Template for the Intervention Description and Replication (TIDieR) framework, an international team developed guidance for comprehensive reporting of trial interventions in pediatric RCT protocols and reports. We (1) identified initial pediatric considerations (PCs) and examples of good reporting using 50 recent pediatric RCT reports, (2) held an expert panel meeting, (3) conducted a Family Caregiver Workshop to discuss and get input on PCs, (4) compiled PCs and examples of good reporting, and (5) achieved consensus on final PCs and examples. Thirteen PCs reached consensus; they address how trial intervention materials were appropriate for the age and developmental stage of trial participants, which adjustments to enhance palatability of medications and acceptability of interventions were implemented, and how pediatric-specific dosing was determined. Consensus was also reached on accompanying good reporting exemplars. Presenting a minimum set of considerations pertinent to pediatric trial interventions, the TIDieR-Child & Adolescent Health (TIDieR-C) checklist can help trial authors and evidence end users comprehensively report and appraise tested interventions. It can be used with the pediatric-specific extensions of the Standard Protocol Items for Randomized Trials (SPIRIT) and Consolidated Standards of Reporting Trials (CONSORT): SPIRIT-Children & Adolescents and CONSORT-Children & Adolescents. Uptake of this guidance may lead to improved understanding, replicability, and implementation fidelity of effective trial interventions.
Copyright © 2025 by the American Academy of Pediatrics.